2005
DOI: 10.1007/s00439-005-0070-4
|View full text |Cite
|
Sign up to set email alerts
|

Short/branched-chain acyl-CoA dehydrogenase deficiency due to an IVS3+3A>G mutation that causes exon skipping

Abstract: Short/branched-chain acyl-CoA dehydrogenase deficiency (SBCADD) is an autosomal recessive disorder of L: -isoleucine catabolism. Little is known about the clinical presentation associated with this enzyme defect, as it has been reported in only a limited number of patients. Because the presence of C5-carnitine in blood may indicate SBCADD, the disorder may be detected by MS/MS-based routine newborn screening. It is, therefore, important to gain more knowledge about the clinical presentation and the mutational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…It has been shown that 5Јss with disease-causing +3 A-to-G mutations exhibit two distinct features: (1) They are intrinsically weak (Madsen et al 2006); and (2) they frequently have nonconsensus nucleotides at positions +4 and +5 (for confirmation, see Fig. 4; Ohno et al 1999;Madsen et al 2006). Figure 4 also shows that 5Јss with G at position +3 and SNPs with A/G alleles at position +3 prefer consensus nucleotides at +4 and +5, in agreement with the second observation.…”
Section: Disease-causing Mutations At 5јssmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been shown that 5Јss with disease-causing +3 A-to-G mutations exhibit two distinct features: (1) They are intrinsically weak (Madsen et al 2006); and (2) they frequently have nonconsensus nucleotides at positions +4 and +5 (for confirmation, see Fig. 4; Ohno et al 1999;Madsen et al 2006). Figure 4 also shows that 5Јss with G at position +3 and SNPs with A/G alleles at position +3 prefer consensus nucleotides at +4 and +5, in agreement with the second observation.…”
Section: Disease-causing Mutations At 5јssmentioning
confidence: 98%
“…For this study, we used 595 disease-causing 5Јss mutations from the HGMD database (Stenson et al 2003) plus another independent set (Madsen et al 2006), excluding mutations that affect the nearly invariant +1 and +2 positions.…”
Section: Disease-causing Mutations At 5јssmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Madsen et al (2006) recently pointed out that a +3A>G mutation causes exon skipping only in the context of a suboptimal 5¢ splice site, with non-conserved bases mainly at positions +4 and +5, in order to ensure efficient base pairing to U1 snRNA during the splicing process. In agreement with this, the 5¢ splice site of PCCA exon 13 has non-matching nucleotides to U1 snRNA at positions +5 and +6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first patient with SBCADD was reported in 1999 [50]. The ACADSB gene structure was described in 2000 [51], and several mutations in this gene have been reported [49,52,53]. In individuals with this disease, urine analysis reveals marked elevations of 2-methylbutyrylglycine [51,54].…”
Section: Iva Newborn Screening: Diagnosis Birth Prevalence and Diffementioning
confidence: 99%